Estimating lifetime pesticide exposure and neurobehavioral performance among mosquito control workers in Malaysia - Yusof, Muhammad Zubir; Semple, Sean; Cherrie, John W.; Samsuddin, Niza (2015)
Use of pesticides has been linked to neurobehavioral deficits among exposed workers. Organophosphate and pyrethroid pesticides are commonly used to control mosquito-borne diseases in Malaysia with a comprehensive spraying programme operated since the 1950s. This project aims to estimate workers’ lifetime exposure to pesticides using current measurements and retrospective exposure reconstruction methods. A total of 160 workers who had regular contact with pesticides and 179 office-based workers were recruited to the study. Information on past exposure and job tasks were collected through questionnaire and occupational history interview to help reconstruct workers’ historical exposures Personal inhalation and dermal exposure measurement were also carried out to evaluate current pesticide exposure. Subjective inhalation exposure modelling using information on the determinants of exposure was used to estimate current exposures and compare these to measured values for calibration of the model. Total lifetime cumulative exposure was then assessed for each worker. The mean age was 30 ± 8 years for mosquito control workers and 31 ± 8 years for office based workers. The highest current level of airborne concentration was identified during thermal spraying and mixing by using organophosphates (Thermal spraying = 0.34 mg/m3; and Mixing = 0.18 mg/m3). Total cumulative pesticides inhalation exposure ranged from 0.0002 to 8.91 OEL.years with a median value of 0.96 (IQR= 0.32 – 1.97). General worker aka ‘Fogger’ had the highest estimated cumulative inhalation exposure (median=1.31 OEL.years, IQR = 0.72 – 2.25). Years of working with pesticides was a moderate predictor of lifetime cumulative exposure as indicated by a Spearman’s correlation coefficient of 0.63. A model to estimate the exposure and uptake of pesticide through the skin was also used. This both inhalation and dermal models were used to allow the estimation of combined pesticide exposure for each exposed worker to explore its relationship with neurobehavioral performance. The analysis for dermal and combined exposure are still underway and the final results will be presented during symposium.